Controls on petroleum stability in deep and hot reservoirs: A case study from the Tarim Basin. (January 2023) - Wang, Daowei; Cai, Chunfang; Yun, Lu; Liu, Jingyan; Sun, Peng; Jiang, Ziwen; Peng, Yanyan; Zhang, Hao; Wei, Tianyuan; Pei, Bingbing
Abstract: Petroleum stability varies greatly among different basins with light oil recently being produced from reservoirs at depths up to 8260 m and present bottom hole temperatures up to 171 °C in the Tarim Basin. Determining the extent of oil-gas conversion (EOGC) and its controls are crucial to the "exploration deadline" of temperature or depth for liquid hydrocarbons. For this purpose, about 90 oils from the Cambrian and Ordovician in the Tarim Basin have been analyzed for biomarkers, diamondoids and thiadiamondoids, and their gas/oil ratios were collated. These oils have EOGC from 45.4 to 98.3% for TSR-altered oils in the Tazhong and Shunbei areas, and only 0–49.2% for all other non-TSR oils. Among non-TSR-altered oils, Tazhong oils show higher EOGC values (28.0–49.2%) than those in Tabei (0–9.7%) and Shunbei (0–32.7%) oils, respectively. We propose that higher heating rates (7 °C/Ma) and shorter durations (<5 Ma) at high temperatures (>150 °C) may account for the lower EOGC values of oils in the Tabei and Shunbei areas than those in the Tazhong with values of 0.1 °C/Ma and 250 Ma (>120 °C), respectively. The oil may be completely converted to methane-dominated gas if it was exposed to high temperatures for a longer duration as exampled from gas pools from the Lower Cambrian in the Sichuan Basin. In this case, the oil was heated at a rate of 1 °C/Ma since the oil charge and experienced >200 °C for about 50 Ma. Thermochemical sulfate reduction may have enhanced the conversion of oil to gas, leading to an increase in EOGC values from 30% for non-TSR-altered oils to 98% for the strongly TSR-altered oil in the eastern Tazhong area with similar burial-heating history. A similar case for elevated EOGC due to TSR can be found in the Smackover Formation, Gulf of Mexico. Thus, two global models related to heating rate and duration at high temperatures and TSR are developed to illustrate oil stability with temperature and are expected to be instructive for deep petroleum exploration. Highlights: The extents of oil-gas conversion in the Tarim Basin vary widely in different areas. Higher heating rates and shorter durations at high temperatures may favor the preservation of oil. TSR could lower oil and gas stability and accelerate the conversion of oil to wet gas and of wet gas to dry gas. Two global models are developed to illustrate oil stability with temperature.